(untitled) (International Journal of Engineering Materials and Manufacture, 2025)
The growing demand for sustainable requirements in all disciplines that should be aligned with the concept of smart cities with parallel of the need to achieve the united nation sustainable development goals by 2030, leads the researchers to find innovative solution in circular economy based. One of the new technologies that have wide range of application due to its variety of application is the Glass optical Fibers. Optical Fibers have a contribution to different industries such communication, construction and manufacturing. This led to a huge quantity of waste based on the linear economy concept. This research focus on highlighting the contribution of recycled glass as a sustainable alternative to virgin silica, emphasizing its ability to retain essential properties. Furthermore, the adoption of recycled glass aligns with circular economy principles, enabling resource conservation, reduced environmental degradation, and energy-efficient manufacturing. The research also highlighted the challenging for recycling the optical Fiber-based glass. By addressing these challenges, recycled glass optical fibres contribute significantly to achieving multiple Sustainable Development Goals (SDGs). Moreover, the critical role of recycled glass in fostering eco-friendly and technologically advanced smart city infrastructures while promoting sustainability, efficiency, and environmental stewardship in modern urban development also was discussed. As a result, Glass-based fibre optics support growing smart city needs, increasing their use and resulting waste, which should be viewed as a valuable resource, not environmental burden.